New evidence that vitamin D prevents headache: a bidirectional two-sample Mendelian randomization analysis - Xiong, Haibing; Jiang, Ran; Xing, Lingzhi; Zheng, Jiaojiao; Tian, Xinhong; Leng, Jiajie; Guo, Xin; Zeng, Shi; Xiong, Haofeng; Huo, Jianhong; Li, Letai (Frontiers in Neurology, 2024)
Background Previous observational clinical studies and meta-analyses have yielded inconsistent results regarding the relationship between vitamin D and headache, and the causal relationship remains unclear. The aim of this study was to investigate the causal relationship between vitamin D and headache by bidirectional two-sample Mendelian randomisation (MR) analysis. Methods The relationship between high levels of vitamin D and headache was investigated by two-sample MR analysis using publicly available genome-wide association study (GWAS) data. The primary method was inverse variance weighting (IVW), and secondary methods were weighted median and MR-Egger methods. No heterogeneity or horizontal multidirectionality was found in the MR results. The robustness and validity of the findings were assessed using the leave-behind method. Results A significant causal relationship was found between high vitamin D levels and headache using the IVW method (OR = 0.848; p = 0.007; 95% CI = 0.752–0.956). However, in a reverse analysis, no evidence of a causal relationship between headache and high levels of vitamin D was found using the IVW method (OR = 1.001; p = 0.906; 95% CI = 0.994–1.006). Our MR analyses showed no significant horizontal multidimensionality or heterogeneity (p > 0.05). Sensitivity analyses confirmed that MR estimates were not affected by single nucleotide polymorphisms (SNPs). Confirmation that our results are robust and valid has been obtained by the leave-one-out method. Conclusion Our study suggests that high levels of vitamin D prevent the risk of headache. However, there is no evidence of a causal relationship between headache and high levels of vitamin D. Vitamin D may reduce the risk of headache.